2015
DOI: 10.2217/fca.14.55
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of Atherosclerosis

Abstract: Atherosclerosis is a chronic, progressive, multifocal disease of the arterial wall, which is mainly fuelled by local and systemic inflammation, often resulting in acute ischemic events following plaque rupture and vessel occlusion. When assessing the cardiovascular risk of an individual patient, we must consider both global measures of disease activity and local features of plaque vulnerability, in addition to anatomical distribution and degree of established atherosclerosis. These parameters cannot be measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 129 publications
0
15
0
1
Order By: Relevance
“…One such method is 18F-fluorodeoxyglucose Positron Emission Tomography (18F-FDG PET) combined with computed tomography (CT), which has been used in both preclinical and clinical studies for the evaluation of inflammation in the arterial wall [18,19,20,21,22]. Over the last few years, significant technical progresses have been achieved in order to extend the CV applications of 18F-FDG PET/CT, which include improved image acquisition, measurements, and reconstruction protocols [23].…”
Section: Introductionmentioning
confidence: 99%
“…One such method is 18F-fluorodeoxyglucose Positron Emission Tomography (18F-FDG PET) combined with computed tomography (CT), which has been used in both preclinical and clinical studies for the evaluation of inflammation in the arterial wall [18,19,20,21,22]. Over the last few years, significant technical progresses have been achieved in order to extend the CV applications of 18F-FDG PET/CT, which include improved image acquisition, measurements, and reconstruction protocols [23].…”
Section: Introductionmentioning
confidence: 99%
“…A number of clinical trials have indicated its value as a surrogate marker of treatment efficacy [58], for example using statins [59,60] or lipoprotein apheresis [61], while for niacin added to statin therapy, no additional benefi t was reported [62]. Particular problems arise when F-18-FDG is used in coronary artery lesions; several attempts have been made to improve the results, including a rather strict dietary intervention such as a one day high-fat low carbohydrate diet prior to scanning [63,64] to decrease myocardial glucose uptake as well as motion correction [65,66].…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…In addition, small business innovative research (SBIR) grants and small business technology transfer (STTR) grants can provide the funds to demonstrate proof of concept for innovative device projects that involve more research or risk than the market will generally tolerate. (22)…”
Section: Funding and Return On Investmentmentioning
confidence: 99%